Three resorcin[4]arene-based lanthanide-coordination polymers with multifunctional photoluminescence sensing properties. Issue 7 (28th January 2019) - Zhang, Hang; Wang, Jia-Chen; Jiang, Wei; Zhao, Si-Si
Abstract : We report three lanthanide-coordination polymers assembled with a resorcin[4]arene ligand, where1 and2 could be applied as fluorescent sensors for N, N ′-dimethylformamide and Fe 3+ ion. Abstract : By utilizing a novel octacarboxylate-functionalized resorcin[4]arene as organic linkers, three lanthanide-coordination polymers, namely, [(CH3 )2 NH2 ][Ln2 (HL)(H2 O)7 ]·2H2 O (Ln = Tb (1 ), Eu (2 ) and Gd (3 ), H8 L = 2, 8, 14, 20-tetra-pentyl-4, 6, 10, 12, 16, 18, 22, 24-octa-carboxymethoxy-resorcin[4]arene) have been solvothermally synthesized and structurally characterized. Isostructural1–3 display unique two dimensional sandwich-based layers built with Ln 3+ cations and bowl-shaped HL 7− anions. Remarkably, 1 and2 produce intensive green and red emissions respectively and long lifetimes thanks to the antenna effect of HL 7− anions. The energy level testing of3 indicates that the newly designed ligand H8 L has a very efficient intersystem crossing process. More importantly, luminescent investigations reveal that1 and2 can selectively detect N, N ′-dimethylformamide and Fe 3+ ions with turn-on-type and turn-off-type responses, respectively.